2020
DOI: 10.1007/s00271-020-00708-w
|View full text |Cite
|
Sign up to set email alerts
|

Soil electrical resistivity monitoring as a practical tool for evaluating irrigation systems efficiency at the orchard scale: a case study in a vineyard in Central Chile

Abstract: In many orchards, irrigation scheduling is designed based on data from meteorological networks and considering homogeneous soil properties. Such assumptions may result in inefficient irrigation, which is difficult to constrain without expensive or invasive techniques. Here we have evaluated the ability of the electrical resistivity tomography (ERT) for detecting meterscale irrigation uniformity and deep percolation during irrigation. The spatiotemporal variability of soil volumetric water content (VWC) in a vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Soil sampling below 2 m was recommended in peach orchards [44] to ensure that plant roots were not affecting the accumulation of salts. In additional studies [45], water and nutrient movement has been shown to be variable up to 1 m below drip irrigation sources in vineyards. Future studies with Atriplex should aim to collect soil samples at 2 m or deeper to track salt accumulation with depth and to determine if the root uptake or leaching of ions is occurring below the rootzone.…”
Section: Discussionmentioning
confidence: 97%
“…Soil sampling below 2 m was recommended in peach orchards [44] to ensure that plant roots were not affecting the accumulation of salts. In additional studies [45], water and nutrient movement has been shown to be variable up to 1 m below drip irrigation sources in vineyards. Future studies with Atriplex should aim to collect soil samples at 2 m or deeper to track salt accumulation with depth and to determine if the root uptake or leaching of ions is occurring below the rootzone.…”
Section: Discussionmentioning
confidence: 97%
“…In agricultural research, electrical resistivity tomography (ERT) is increasingly being used for monitoring soil moisture content (Rao et al., 2020), evaluating the effectiveness of irrigation systems on field scale through the spatio‐temporal variation of soil moisture content (Araya et al., 2021), and, as recently reviewed by Cimpoiaşu et al. (2020), the relationship between resistivity and water uptake by plants under different irrigation conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, ERT has not been frequently used at agricultural scales; however, more recently, ERT has increasingly been applied to monitor the dynamics of soil salinity (Walter et al., 2018), soil moisture content (Rao et al., 2020), or water uptake by plants to improve water management (Araya Vargas et al., 2021), and as recently reviewed by Cimpoiaşu et al. (2020), the structure of the root zone.…”
Section: Introductionmentioning
confidence: 99%